An estimation of triaxial forces from normal stress tactile sensor arrays - Pinto-Salamanca, María L.; Castellanos-Ramos, Julián; Pérez-Holguín, Wilson J.; Hidalgo-López, José Antonio (Elsevier, 2023)
This work proposes a new method to find an optimal solution of the inverse problem of the Boussinesq equation for ill-posed problems, applicable in the reconstruction of triaxial forces for processing contact data in tactile decoding systems. This paper focuses on the estimation of triaxial forces from normal stress tactile sensor arrays on flat non-deformable surfaces for single static contacts. This method estimates a triaxial force vector on the sensor coverage surface for each stress value from the relation between the stress data and the applied normal and tangential contact forces. The main contribution of this work consists of a new procedure for estimating contact forces simplifying both arithmetic operations and the optimization process used. Because of this, obtaining a force estimation has a predictable computation time, which makes this new method an attractive solution for implementation in hardware-based real-time tactile sensing systems. The verification process was conducted using a Finite Element Analysis (FEA) as a reference. When testing tactile sensors in a range of sizes and resolutions for piezoelectric and piezoresistive technologies, a maximum estimation error of 10.93% was obtained, including errors due to the array discretization.
Keywords: Electrónica; Detectores; Efecto Volta; Detección de señales; Contact forces reconstruction; Model-driven; Normal stress; Tactile sensor array